Kreativitas Seni: Penerapan Batik Cap Pada Anak Usia Dini - Tri Wahyu Martiningsih; Zyailia Romdania (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This classroom action research aims to improve the artistic creativity of children in Group B of RA Fathus Salafi, Mangaran District, Situbondo Regency, through the application of stamped batik techniques using banana stems. In the context of stamped batik application, the teacher's role is to provide structured support, such as demonstrating stamping techniques, assisting with color selection, and providing pattern ideas. The study employed a cyclical Classroom Action Research design (Pre-Cycle, Cycle I, Cycle II) with 19 early childhood children aged 5-6 years. Data analysis used descriptive, interpretive qualitative data analysis based on participant observation data, field notes, and documentation. Quantitative data analysis was used to measure improvements in creativity learning outcomes between research cycles. The results showed a significant increase in creativity, from 25% (Pre-Cycle) to 63.15% (Cycle I) and then to 84.21% (Cycle II) after the final action. Thus, the application of stamped batik is expected to optimally stimulate the development of artistic creativity in early childhood through socially and culturally rich learning experiences.